2013
DOI: 10.1136/jclinpath-2013-201448
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of CDX1, CDX2 and SOX2 in patients with gastric cancer also affects the non-malignant mucosa

Abstract: The interplay between gastric and intestinal transcription factors has an important impact on gastric carcinogenesis. We compared the gene expression of CDX1, CDX2, SOX2 and related downstream genes in tumour and tumour surrounding gastric tissue of 48 gastric cancer patients with 30 healthy controls. There was no difference of gene expression of CDX1 and CDX2 between tumour or tumour-adjacent and tumour-distant mucosa, but both factors were significantly higher expressed in cancer patients compared with contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…CDX2 has a tumour suppressor role and is known to regulate intestinal differentiation . Induction of CDX2 appears to be an early event in the progression of gastric cancer of the intestinal and diffuse type, and thus CDX2 negativity in our cases suggests that these lesions probably develop along a different pathway of tumorigenesis.…”
Section: Discussionmentioning
confidence: 76%
“…CDX2 has a tumour suppressor role and is known to regulate intestinal differentiation . Induction of CDX2 appears to be an early event in the progression of gastric cancer of the intestinal and diffuse type, and thus CDX2 negativity in our cases suggests that these lesions probably develop along a different pathway of tumorigenesis.…”
Section: Discussionmentioning
confidence: 76%
“…Under normal conditions, the expression of CDX2 was detected in IM but was absent in normal gastric cells [48]. In previous studies, researchers showed that the up-regulation of CDX2 expression during IM is important in the determination of the incomplete type of IM (type IIb, III) and early-stage GC, which had also been demonstrated in animals [4952]. However, the regulation of CDX2 in GIM remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It is caused naturally by the remnant stomach, which is preserved after ER. In addition, the surrounding non-tumorous mucosa may be at high risk of developing metachronous gastric lesions because it used to share the environment with gastric cancer [ 28 ]. Therefore, eradication of H .…”
Section: Discussionmentioning
confidence: 99%